Tear film disorders as a manifestation of various diseases and conditions - Niezgoda, Łucja; Fudalej, Ewa; Nowak, Anna; Kopacz, Dorota (Klinika Oczna / Acta Ophthalmologica Polonica, 2020)
The tear film consists of multiple layers, traditionally categorized as three separate units (the outermost lipid layer, the middle aqueous layer and the innermost mucins). Each building substance of the tear film has a specific role in its proper functioning and is prone to certain disturbances caused by both local and general disorders. A systematic review of the recent literature was conducted, with data obtained via PubMed. The authors focused on tear film disorders as a manifestation of various diseases and conditions, with consideration of the current classification and diagnostic approaches. The elaborate composition of the ocular surface results in the diversity of problems affecting it. Bearing in mind the extensiveness of the subject, the most common and clinically important defects were selected. Defining the etiology of some disturbances can be very complex, but it is crucial for proper diagnosis and treatment.